Investigation of block matching algorithm for video coding - Faizul Hadi Mohamad Jamil (2013)
The model of advanced video coding technique can be divided into two main parts that are the spatial model and the temporal model. The Spatial model exploits the redundancy in a single video frame (I frame) while the temporal model exploits the redundancy among frames (P frame). The temporal model deals with motion estimation (ME) and motion compensation (MC) algorithm with the matching technique called “Block Matching Algorithm” (BMA) to produce the next encoded video frame with motion vector. In this research, seven types of famous BMA techniques that are Exhaustive Search (ES), Three Step Search (TSS), New Three Step Search (NTSS), Simple and Efficient Three Step Search (SETSS), Four Step Search (4SS), Diamond Search (DS) and Adaptive Rood Pattern Search (ARPS) have been applied. These techniques have been used to analyze the video frames quality with different Macroblock size and different sequence of I and P frame and also with different search ranges of block prediction. Then, the best BMA algorithm technique will be chosen to develop a hybrid method that varies with the motion type of the video. This method will detect whether the video has a high, medium or low motion movement and it will determine the suitable Macroblock size (MB) and search range (p) for it. By using the hybrid method, it shows that the high motion video requires small MB size and larger search range to gain high encoded video quality while for the low motion video, larger MB size and small search range can be used to generate an acceptable video quality. Overall, this hybrid method can produce high quality video for the high motion movement video and it can reduce the computational complexity and yield to an acceptable quality for the low motion video.